Pengendalian Proyek Pembangunan Lanjutan SMA Negeri Internasional Sumatera Selatan Palembang dengan Metode Earned Value - Gusti Rahma Dini; Ika Juliantina (Jurusan Teknik Sipil Fakultas Teknik Universitas Sriwijaya, 2013)
The construction of developing in Palembang is getting bigger and complicated both in the cost and the time consuming now. For instance, the developing project of SMA Negeri Internasional South Sumatera Palembang, that has the restriction in term of the funishing time. The concept of Earned Value combines the schedule, cost and the achievement, in order to detect the prediction of time and cost to finish a project. This method is also used to detect the earliest out budget that probably happens and the project will probably be late. BCWP, BCWS, and ACWP are the basic indicators that has been a main point to analyse the performance of working based on the concept of Earned Value. This procedure is begun by doing the literature study, tabulating data, observing the project and summarizing the data. The data processing and the final review (week – 13), the value of SPI reaches 1,14 this project has been increasing to 11,347% from the plan target 78,937% and realization of work 90,284% in term of the cost project, CPI is 0,99 means the cost project that has been spending already bigger from the plan. Meanwhile, finishing will be done for 92 days, it means the time is a little faster from the organized schedule for 105 days.Key Words : Earned Value, BCWS, BCWP, ACWP